Inaugural meeting of the Global Alliance on Climate-Smart Agriculture, 24 September 2014, New York City - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Inaugural meeting of the Global Alliance on Climate-Smart Agriculture, 24 September 2014, New York City.